MOTIVATION AND LEARNING ENGAGEMENT THROUGH PLAYING MATH VIDEO GAMES - Daisyane Barreto; Lucas Vasconcelos; Michael Orey (UUM Press, 2017)
Purpose - With video games being a source of leisure and learning, educators and researchers alike are interested in understanding childrenâ€™s motivation for playing video games as a way to learn. This study explores student motivation and engagement levels in playing two math video games in the game Club Penguin. Method - This is a qualitative case study conducted in a North American elementary school after-school program. It involves two children ages eight and nine playing math games. Data sources in this study include interviews, observations and video recordings of game playing. Findings - Participants in this study are not always motivated to play math video games. They can sustain engagement in game playing for seven to twelve minutes before seeking another game or activity. Participants show some signs of disengagement during math game playing. Significance - Findings from this study can inform teachers, parents and instructional designers about what impacts childrenâ€™s motivation and engagement levels while playing math video games.